STUDENTS’ PERCEPTIONS OF TAX EVASION ARE INFLUENCED BY THEIR UNDERSTANDING OF TAX RATES AND TAX SANCTIONS - Armitha Nisa; Rita Dwi Putri; Siska Yulia Defitri (Jurnal Ekonomi, 2023)
Tax evasion in Indonesia itself is still widely practiced. Students who will later become taxpayers (WP) need to understand and about the tax rates that must be paid and the sanctions that are obtained if they are negligent in paying taxes. So that tax evasion in Indonesia can be avoided. This study aims to determine the effect of an understanding of tax rates and an understanding of tax sanctions on perceptions of tax evasion. This type of research is quantitative research with an associative approach. The population of this study were students of the Mahaputra Muhammad Yamin University Accounting Study Program who were active and registered in the odd semester of the 2022/2023 academic year. The sampling technique used was purposive sampling. The data used is primary data obtained from questionnaires distributed through the Google Form. Partially, the results of the study show that an understanding of tax rates influences perceptions of tax evasion and an understanding of tax sanctions influences perceptions of tax evasion. Meanwhile, simultaneously, an understanding of tax rates and tax sanctions influences perceptions of tax evasion.